Сучасний аналітичний контроль якості цукру - Скорик, Костянтин Дмитрович (My University, 2006)
Розглянуто питання гармонізації вимог до якості цукру в Україні з міжнародними вимогами. Звертається увага на необхідність мікробіологічного контролю цукрового виробництва. Наведені деякі особливості проведення вимірюваннь кольоровості і кондуктометричної золи в білому цукрі. Issues are discussed of harmonization of sugar quality requirements in Ukraine with international requirements. Attention was paid to necessity of microbiological control of sugar production. Some peculiarities are presented as for carrying out measurements of color and conductometric ash in white sugar.
Keywords: методики аналізів цукру; мікробіологічний контроль; прилади; колориметр; кондуктометр; methods of sugar analysis; microbiological control; instruments; colorimeter; conductivity meter